Community Participation in Native American and White Individuals After Traumatic Brain Injury: A 5‐Year Longitudinal Model Systems Study - Jack D. Watson; Paul B. Perrin; Bridget Xia; Juan Carlos Arango‐Lasprilla (Brain and Behavior)
Abstract Purpose/Objective This study examined (a) differences in demographic and injury‐related characteristics following traumatic brain injury (TBI) between Native American and White individuals; (b) differences in community participation between Native American and White individuals with TBI at 1, 2, and 5 years after TBI; and (c) whether demographic or injury‐related characteristics account for community participation disparities. Research Method/Design A sample of 63 Native American individuals demographically matched to 63 White individuals (n = 126) was enrolled while on acute rehabilitation for moderate or severe TBI. Baseline demographic and injury‐related characteristics were collected at this time and the Participation Assessment with Recombined Tools (PART‐O) measure of community participation at 1, 2, and 5 years after TBI. Results Native American individuals were less likely to have private insurance and be employed at the time of injury and more likely to have had lower educational attainment and engaged in binge drinking in the month prior to TBI compared to White individuals. Native American individuals demonstrated lower Out and About scores but statistically equivalent Social and Productivity scores. The difference in Out and About scores did not change as a function of time, and the overall difference between the two groups dissipated with the inclusion of statistically different sociodemographic variables. Conclusions/Implications Clinicians can provide culturally sensitive, patient‐ and family‐centered care by conducting comprehensive interviews and identifying strengths as well as risk factors that enhance or hinder community participation after TBI in Native American individuals.